1988
DOI: 10.1063/1.454802
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism in poly(3-hexylthiophene) in the solid state: A spectroscopic study of temperature-dependent conformational defects

Abstract: Reversible thermochromism in thin solid films of poly(3-hexylthiophene), or P3HT, has been studied using ultraviolet and x-ray photoelectron spectroscopies (UPS and XPS, respectively). The UPS and XPS spectra, as well as previously published optical absorption spectra, are analyzed using the results of valence effective Hamiltonian (VEH) quantum chemical calculations of the electronic structure of isolated polymer chains. The analysis of the spectra indicates that at elevated temperatures thermally induced ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
114
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(129 citation statements)
references
References 31 publications
10
114
1
4
Order By: Relevance
“…We assign this feature of -1.7 eV to a defect state, which could be a consequence of impurities and/or "chemical" defects, although this feature has been ascribed to band structure effects accompanying the ordering of the aromatic chain backbone. 1 The nature of the "defects" that lead to this state cannot be uniquely identified from our data, although there are several possibilities. As seen in Figure 3, limited loss of regioregularity (Figure 3a), an oxygen bridging two pendant groups (Figure 3b), selected dehydrogenation resulting in a pendant group linking two adjacent thiophenes (Figure 3c), and loss of π-π stacking either through tilting of adjacent polymer chains (Figure 3d) or as a result of a lateral displacement of adjacent polymer chains (Figure 3e) could well result in the appearance of defects states within the HOMO-LUMO gap of regioregular poly(3-hexylthiophene-2,5 diyl) (P3HT).…”
Section: Evidence For Dielectric Character Of P3htmentioning
confidence: 89%
See 3 more Smart Citations
“…We assign this feature of -1.7 eV to a defect state, which could be a consequence of impurities and/or "chemical" defects, although this feature has been ascribed to band structure effects accompanying the ordering of the aromatic chain backbone. 1 The nature of the "defects" that lead to this state cannot be uniquely identified from our data, although there are several possibilities. As seen in Figure 3, limited loss of regioregularity (Figure 3a), an oxygen bridging two pendant groups (Figure 3b), selected dehydrogenation resulting in a pendant group linking two adjacent thiophenes (Figure 3c), and loss of π-π stacking either through tilting of adjacent polymer chains (Figure 3d) or as a result of a lateral displacement of adjacent polymer chains (Figure 3e) could well result in the appearance of defects states within the HOMO-LUMO gap of regioregular poly(3-hexylthiophene-2,5 diyl) (P3HT).…”
Section: Evidence For Dielectric Character Of P3htmentioning
confidence: 89%
“…On the basis of the photoemission results, Salaneck and co-workers 1,2 proposed that the thiophene rings are coplanar at low temperatures and the torsion angle or disorder along the aromatic backbone increases with increasing temperature, and these structure changes occur near or above room temperature. [1][2][3] From the light polarizationdependent photoemission, we infer that changes in the regioregular P3HT polymer backbone geometry occur well below room temperature for P3HT, and the structure changes are gradual. Other conducting polymers exhibit changes in the orientation of the aromatic rings in the polymer backbone with temperature similar to those reported here for P3HT, including polypyrrole, 4 so P3HT is not unusual in this regard.…”
Section: Structural Changes In the P3ht And Pedot Aromatic Chain Backmentioning
confidence: 92%
See 2 more Smart Citations
“…Thermochroism studies on poly(3-alkylthiophenes) identified the cause for the strong hypsochromic shift with increasing temperature to be an increasing twist between adjacent thiophene units. 17 A similar effect comes into play for P3TOT. For this type of molecule, a preferential ordering of the side chains within the plane of the main polymer backbone is expected.…”
mentioning
confidence: 81%